2009
DOI: 10.3945/ajcn.2009.26736n
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of vegan diets

Abstract: Recently, vegetarian diets have experienced an increase in popularity. A vegetarian diet is associated with many health benefits because of its higher content of fiber, folic acid, vitamins C and E, potassium, magnesium, and many phytochemicals and a fat content that is more unsaturated. Compared with other vegetarian diets, vegan diets tend to contain less saturated fat and cholesterol and more dietary fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
344
0
47

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 464 publications
(397 citation statements)
references
References 101 publications
6
344
0
47
Order By: Relevance
“…This type of study must be recognised for having a signalling function. In the case of a shift of children's diets towards lower intakes of meat and/or dairy, nutritional status analyses are needed to confirm adequacy of intakes of Zn, thiamin, vitamin B 12 and probably Fe by the true prevalence of marginal nutritional statuses. Starting from the current consumption patterns of Dutch children, the choice of savoury (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of study must be recognised for having a signalling function. In the case of a shift of children's diets towards lower intakes of meat and/or dairy, nutritional status analyses are needed to confirm adequacy of intakes of Zn, thiamin, vitamin B 12 and probably Fe by the true prevalence of marginal nutritional statuses. Starting from the current consumption patterns of Dutch children, the choice of savoury (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…When full replacements are made, attention is recommended to ensure adequate thiamin, vitamin B 12 and Zn in children's diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of trace elements in hair have been shown to reliably reflect long term nutritional status [15]. Dietary sources of zinc are mainly from high protein foods such as red meats and seafood, and as such the vegetarian diet is prone to lead to deficiency [30]. High levels of selenium are found in brazil nuts, kidney, seafood and cereals, although this is soil dependent and it has been reported that European intake of selenium is falling [31].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that well-planned vegetarian diet provides numerous health benefits and is appropriate for all stages of life cycle [2]. Considering health hazards of consumption of protein rich diet deriving from animal sources, proportion of vegetarian or people consuming vegetable-based diet is increasing globally [3], [4], [5], [6]. Global health economy is recently experiencing high burden of chronic diseases as cardiovascular diseases, cardiovascular disease as well as endocrine disorders like diabetic mellitus with sufferings from malignancy [7], [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%